Case Report: Posterior Ischemic Optic Neuropathy - Kwon, Hyukjin; MacIver, Sarah (Canadian Journal of Optometry, 2020)
Purpose: To report on posterior ischemic optic neuropathies, a vascular disorder that happens in the posterior part of the optic nerve and therefore, usually does not present with optic disc edema. Case Report: This is a case report on a posterior ischemic optic neuropathy with an uncharacteristic presentation. It highlights the importance of understanding the different pathophysiology of PION vs anterior ischemic optic neuropathies in order to help differentiate the two clinically and includes a literature review of posterior ischemic optic neuropathy.